An investigation of the interactions of Eu3+ and Am3+ with uranyl minerals: implications for the storage of spent nuclear fuel. Issue 15 (30th March 2016) - Biswas, Saptarshi; Steudtner, Robin; Schmidt, Moritz; McKenna, Cora; León Vintró, Luis; Twamley, Brendan; Baker, Robert J.
Abstract : Eu(iii ) can incorporate into the structure of selected uranyl minerals, as shown emission and vibrational spectroscopy. 241 Am(iii ) tracer studies have been conducted, which has implications for the migration of Am(iii ) in an underground repository containing SNF. Abstract : The reaction of a number of uranyl minerals of the (oxy)hydroxide, phosphate and carbonate types with Eu(iii ), as a surrogate for Am(iii ), have been investigated. A photoluminescence study shows that Eu(iii ) can interact with the uranyl minerals Ca[(UO2 )6 (O)4 (OH)6 ]·8H2 O (becquerelite) and A[UO2 (CO3 )3 ]· x H2 O (A/ x = K3 Na/1, grimselite; CaNa2 /6, andersonite; and Ca2 /11, liebigite). For the minerals [(UO2 )8 (O)2 (OH)12 ]·12H2 O (schoepite), K2 [(UO2 )6 (O)4 (OH)6 ]·7H2 O (compreignacite), A[(UO2 )2 (PO4 )2 ]·8H2 O (A = Ca, meta -autunite; Cu, meta -torbernite) and Cu[(UO2 )2 (SiO3 OH)2 ]·6H2 O (cuprosklodowskite) no Eu(iii ) emission was observed, indicating no incorporation into, or sorption onto the structure. In the examples with Eu 3+ incorporation, sensitized emission is seen and the lifetimes, hydration numbers and quantum yields have been determined. Time Resolved Laser Induced Fluroescence Spectroscpoy (TRLFS) at 10 K have also been measured and the resolution enhancements at these temperatures allow further information to be derived on the sites of Eu(iii ) incorporation. Infrared and Raman spectra are recorded, and SEM analysis show significant morphology changes and the substitution of particularly Ca 2+ by Eu 3+ ions. Therefore, Eu 3+ can substitute Ca 2+ in the interlayers of becquerelite and liebigite and in the structure of andersonite, whilst in grimselite only sodium is exchanged. These results have guided an investigation into the reactions with 241 Am on a tracer scale and results from gamma-spectrometry show that becquerelite, andersonite, grimselite, liebigite and compreignacite can include americium in the structure. Shifts in the UO and C–O Raman active bands are similar to that observed in the Eu(iii ) analogues and Am(iii ) photoluminescence measurements are also reported on these phases; the Am 3+ ion quenches the emission from the uranyl ion.